One piece. Collection 22 [videorecording (DVD)] - Miyamoto, Hiroaki (FUNimation, 2017)
Armed with newfound strength, the Straw Hats reunite in Sabaody Archipelago and begin their journey to the New World. Heading underwater, they2ll have to take on the cantankerous creatures of the deep sea before reaching their next stop, Fish-man Island. After a rough landing scatters the pirates, a good deed earns them an invitation to the royal palace. Everything goes swimmingly until a psychic2s prophecy turns the whole island against Luffy and his crew.